The Mobile Phone in the Diffusion of Knowledge for Institutional Quality in Sub-Saharan Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
This study assesses the mobile phone in the diffusion of knowledge for better governance in sub-Saharan Africa for the period 2000-2012. For this purpose we employ Generalised Method of Moments with forward orthogonal deviations. The empirical evidence is based on three complementary knowledge diffusion variables (innovation, internet penetration and educational quality) and ten governance indicators that are bundled and unbundled. The following are the main findings. First, there is an unconditional positive effect of mobile phone penetration on good governance. Second, the net effects on political, economic and institutional governances that are associated with the interaction of the mobile phone with knowledge diffusion variables are positive for the most part. Third, countries with low levels of governance are catching-up their counterparts with higher levels of governance. The above findings are broadly consistent with theoretical underpinnings on the relevance of mobile phones in mitigating bad governance in Africa. The evidence of some insignificant net effects and decreasing marginal impacts may be an indication that the mobile phone could also be employed to decrease government quality. Overall, this study has established net positive effects for the most part. Five rationales could elicit the positive net effects on good governance from the interaction between mobile phones and knowledge diffusion, among others, the knowledge variables enhance: reach, access, adoption, cost-effectiveness and interaction. In a nut shell, the positive net effects are apparent because the knowledge diffusion variables complement mobile phones in reducing information asymmetry and monopoly that create conducive conditions for bad governance. The contribution of the findings to existing theories and justifications of the underlying positive net effects are discussed.
Keywords: G20; O38; O40; O55; P37; 330; Mobile phones; Governance; Africa